Attitudes and Prerequisites for the Establishment of an Integrated Cultural Identity within Romanian-Bulgarian Cross-Border Region along the Danube River - Juliana Popova (Journal of Danubian Studies and Research, 2013)
Objectives: On the basis of the results from an empirical study this research aims at exploration of the prerequisites for the establishment of an integrated cultural identity within Romanian-Bulgarian Cross-Border Region along the Danube River (RBCBR). Prior Work: The paper is trying to prove the necessity of identity re-negotiation process within RBCBR. The theoretical background of the research is related to some of the most topical considerations in this scientific field. Approach: The research uses an interdisciplinary approach and combines the perspectives of regional studies, cross-cultural psychology and intercultural communication. A representative survey is the main instrument of the research. Results: Among the citizens of the RBCBR there exist favourable attitudes towards closer relations with their neighbours which can serve as a key element of the identity re-negotiation process within the region. Implications: The research results can be used by policy makers and regional authorities in the process of establishment of a new policy for territorial cooperation as well as by researchers in further development of this topic area. Value: the importance of the research is in its new approach towards the establishment of integrated regional identity as well as in the comparison of the Romanian and Bulgarian attitudes towards cooperation in the neighbourhood area.